Zastosowanie logiki rozmytej do poprawy efektywności metod wyboru strategii płynności finansowej przedsiębiorstw - Bartkiewicz, Agnieszka; Korniak, Jacek (Fuzzy Logic Application to Improve the Effectiveness of the Methods of Choice of the Financial Liquidity Strategy, 2007)
The automated process of financial management decisions is very difficult because of complexity of factors influencing the effectiveness in this area. But it doesn't mean that some degree of automation is not desirable for realization of decision process more efficiently. The application of some norms, patterns and concrete solutions links the possibility of reduction of time and limitation of some actions in the range of extended economic and financial analysis. In this article the authors have applied elements of fuzzy logic to optimize the choice method of the financial liquidity strategy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 66-77